2021
DOI: 10.7202/1083179ar
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual translation in primary education. Students’ perceptions of the didactic possibilities of subtitling and dubbing in foreign language learning

Abstract: This paper investigates the use of Audiovisual Translation (AVT) as a didactic tool in primary education. Several studies confirm that subtitling and dubbing are beneficial for productive and receptive skills, vocabulary acquisition, translation competence, and learners’ motivation and engagement. However, research in the field has been devoted primarily to university students enrolled in translation and language programmes, and there is a dearth of papers exploring the use of AVT in early educational stages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
10
0
4
Order By: Relevance
“…When quantitative data are triangulated with the information retrieved from the questionnaires, very interesting conclusions can be drawn. First of all, subtitling has proved to be a motivating methodology that arouses the interest of students, as reported by Talaván & Ávila-Cabrera (2015) and Fernández-Costales (2021a). Results underline that students' satisfaction is high: according to the initial questionnaire, 90% of the participants expected subtitling to contribute to the enhancement of their competencies.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…When quantitative data are triangulated with the information retrieved from the questionnaires, very interesting conclusions can be drawn. First of all, subtitling has proved to be a motivating methodology that arouses the interest of students, as reported by Talaván & Ávila-Cabrera (2015) and Fernández-Costales (2021a). Results underline that students' satisfaction is high: according to the initial questionnaire, 90% of the participants expected subtitling to contribute to the enhancement of their competencies.…”
Section: Discussionmentioning
confidence: 70%
“…Studies in the field have reported empirical evidence to support didactic claims that AVT favours vocabulary retention (Danan, 2010;Lertola, 2019b), intercultural awareness (Borghetti, 2011;Borghetti & Lertola, 2014), productive skills (Talaván & Costal, 2017;Talaván & Rodríguez-Arancón, 2018), and fluency (Herrero et al, 2017;Sánchez-Requena, 2016). Recent contributions have also focused on the potential of AVT in bilingual education (Fernández-Costales, 2021b), the combination of subtitling and dubbing in language teaching (Fernández-Costales, 2021a;Talaván & Ávila-Cabrera, 2015), or the promotion of creativity through active AVT (Talaván, 2019).…”
Section: Active Subtitling In the Classroommentioning
confidence: 99%
See 2 more Smart Citations
“…A principios del siglo XXI se produce un punto de inflexión en el uso de la TAV didáctica: se pasa de una aplicación de la misma desde una perspectiva pasiva a otra activa en la enseñanza de lenguas (Couto-Cantero et Pilar Gonzalez-Vera • Integración de la subtitulación activa en el aula: estudio de una intervención educativa al., 2021). Los beneficios del uso didáctico de la TAV desde un planteamiento activo han sido recogidos en estudios realizados dentro del Proyecto TRADILEX (Couto-Cantero et al, 2021;Fernández-Costales, 2021a;Talaván y Lertola, 2022) así como en otros trabajos derivados de colaboraciones mantenidas durante la ejecución del proyecto y que estudian la TAV didáctica en la enseñanza de lenguas (Sánchez-Requena, 2018;Gonzalez-Vera y Hornero Corisco, 2019;Hornero Corisco y Gonzalez-Vera, 2020;Talaván, 2020Talaván, , 2021Fernández-Costales, 2021b;.…”
Section: Introducción Y Marco Teóricounclassified